2023
DOI: 10.1002/jmv.28878
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and ultrastructural analysis of monkeypox virus in skin lesions and in human/animal infected cells reveals further morphofunctional insights into viral pathogenicity

Alberto Paniz‐Mondolfi,
Jason Reidy,
Nina Pagani
et al.

Abstract: Monkeypox (MPOX) is a zoonotic disease that affects humans and other primates, resulting in a smallpox-like illness. It is caused by monkeypox virus (MPXV), which belongs to the Poxviridae family. Clinically manifested by a range of cutaneous and systemic findings, as well as variable disease severity phenotypes based on the genetic makeup of the virus, the cutaneous niche and respiratory mucosa are the epicenters of MPXV pathogenicity. Herein, we describe the ultrastructural features of MPXV infection in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The shape of the JEG‐3 cell nuclei was circular, and cells contained abundant glycogen granules (Figure 3A1–A2). Observed MPXV particles were morphologically consistent with the literature, 12–15 possessing the typical oval coffee bean or brick shape containing an external membrane and biconcave core. Mean longest and smallest diameters were 274 ± 35 and 193 ± 31 nm ( n = 48), and 305 ± 25 and 220 ± 24 nm ( n = 14), for oval coffee bean and brick‐shaped particles, respectively.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The shape of the JEG‐3 cell nuclei was circular, and cells contained abundant glycogen granules (Figure 3A1–A2). Observed MPXV particles were morphologically consistent with the literature, 12–15 possessing the typical oval coffee bean or brick shape containing an external membrane and biconcave core. Mean longest and smallest diameters were 274 ± 35 and 193 ± 31 nm ( n = 48), and 305 ± 25 and 220 ± 24 nm ( n = 14), for oval coffee bean and brick‐shaped particles, respectively.…”
Section: Resultssupporting
confidence: 85%
“…The acquisition of additional membrane of the trans‐Golgi cisternae or plasma membrane causes a change in the state of the virion which becomes wrapped and or wrapped extracellular. Current data on virion morphology are due to transmission electronic microscopy 10–15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other OPXVs, MPXV replicates entirely in the cytoplasm and has similar life cycle steps (Figure 1) [2,[22][23][24][25][26], among which viral DNA replication and intracellular virion wrapping steps are targeted by brincidofovir and tecovirimat, respectively [15] (to be discussed in the next section). By employing electron microscopy, Paniz-Mondolfi et al [27] recently observed typical enveloped virions with brick-shaped morphologies containing surface protrusions in MPXV and abundant melanosomes near viral assembly sites in skin lesions isolated from patients affected by the 2022-2023 outbreak. Of note, there are many outstanding questions that remain unanswered in the MPXV life cycle (Figure 1), for example, the cellular receptor of MPXV and the molecular details of virion morphogenesis and egress.…”
Section: Mpxv Biologymentioning
confidence: 99%